PENGEMBANGAN MEDIA PEMBELAJARAN LUMBU (LUDO MENGENAL BUDAYA) PADA MATA PELAJARAN PENDIDIKAN PANCASILA KELAS V DI SD NEGERI 7 WONOGIRI: Penelitian Pengembangan Media Pembelajaran - Wati, Anicce; Darma, Widia; Suyatno, Tri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Learning about cultural diversity in elementary schools plays an important role inshaping students’ understanding of national identity. However, in reality, students’understanding of Indonesia’s cultural diversity is still not optimal. This is caused bythe use of learning media that is not yet varied and has not been able to activelyengage students, resulting in low student interest in participating in the learningprocess.This study aims to determine the feasibility and effectiveness of the LUMBU(Ludo Mengenal Budaya) learning media on the topic of Indonesian cultural diversityfor fifth-grade elementary school students. The method used in this research isResearch and Development (R&D) with the ADDIE model.The results of this studyindicate that the developed LUMBU (Ludo Mengenal Budaya) learning media iscategorized as highly feasible and effective. The average validation results frommedia experts and language experts reached 90%, which falls into the “veryfeasible” category. Student responses showed a percentage of 93% in the small-scale trial and 90% in the large-scale trial, while teacher responses reached 100%in both stages, all of which are categorized as very feasible. The effectiveness ofthe media was measured through pretest and posttest results, where the small-scaletrial showed a result of 90%, and the large-scale trial showed a result of 78%, bothcategorized as effective.